Addressing the Challenges Encountered by AIDA in Attaining its Aid Activities in Africa as a Foreign Donor - Ibrahimli, Ilaha; Mammadov, Elnur; Mukhtarova, Malahat (ADA University, 2024)
Humanitarian aid is an essential tool for any country to build its reputation in the global arena and to establish political relationships with other countries in order to strengthen and increase their cooperation and support. As a newly established aid organization, the Azerbaijan International Development Agency (AIDA) tries to use its resources to keep pace with the developed countries. This capstone project discusses the challenges faced by Azerbaijan in the representation of AIDA in its humanitarian aid activity in the African region. In order to offer a three-sided approach, the data is driven by the interview sessions with three represented parties: AIDA as a donor, politician from the Mauritius as a recipient country and the expert of Organization for Islamic Cooperation (OIC) as an intermediary organization. It is identified that some drawbacks are lack of efficient logistics management, non-participation of AIDA members in the determination of recipient countries’ demand, deficiency of capacity of AIDA for humanitarian aid, insufficiency of management of aid tracking and non-assessment of corruption risks accurately, and absence of a long-term strategy. Additionally, the study provides some policy options according to the problems mentioned and evaluates various policy alternatives based on the following criteria: effectiveness, efficiency, equity, feasibility, and flexibility. The policy options that the study offers to AIDA in this project should be considered as effective ways to reach their aid goals. Finally, this paper evaluates findings from the examination of AIDA's humanitarian aid operation and makes recommendations based on the evaluation of available policy options.
Keywords: Humanitarian assistance -- Political aspects.; Economic assistance, Azerbaijani -- Administration.; International cooperation -- Political aspects.; Humanitarian assistance -- Africa.; Economic development projects -- Management.; Non-governmental organizations -- Azerbaijan.